Abnormal Ocular Movement With Executive Dysfunction and Personality Change in Subject With Thalamic Infarction: A Case Report - Kim, Ee Jin; Kim, Myeong Ok; Kim, Chang Hwan; Joa, Kyung Lim; Jung, Han Young (Annals of rehabilitation medicine, 2015)
The thalamus, located between the cerebrum and midbrain, is a nuclear complex connected to the cerebral cortex that influences motor skills, cognition, and mood. The thalamus is composed of 50-60 nuclei and can be divided into four areas according to vascular supply. In addition, it can be divided into five areas according to function. Many studies have reported on a thalamic infarction causing motor or sensory changes, but few have reported on behavioral and executive aspects of the ophthalmoplegia of the thalamus. This study reports a rare case of a paramedian thalamus infarction affecting the dorsomedial area of the thalamus, manifesting as oculomotor nerve palsy, an abnormal behavioral change, and executive dysfunction. This special case is presented with a review of the anatomical basis and function of the thalamus.